Spending by primary care practices-does it show what we expect? - James, Marilyn; Stokes, Elizabeth (Wiley, 2013)
Background Over recent years, a number of policies and financial incentives in primary care have been proposed to tackle issues such as deprivation and health outcomes. This article investigates the association between healthcare spending, deprivation and outcomes. It argues that individual practice data are analysed before blanket application and acceptance that one size fits all in a local area.